FINTECH SOLUTIONS FOR GREEN FINANCE: LEVERAGING BLOCKCHAIN AND AI IN FINANCING RENEWABLE ENERGY PROJECTS - Xu Hui; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
Transitioning to a low-carbon economy will require substantial investment in renewable energy projects. Traditional financing modalities, on the other hand, confront difficulties in generating funds and maintaining transparency in the context of green finance. Through blockchain technology and artificial intelligence (AI), this academic study analyses the function of financial technology (Fintech) as a catalyst for sustainable finance. This study has provided an in-depth look at the possibilities of blockchain technology and artificial intelligence in improving financial operations, increasing transparency, and providing innovative solutions for sustainable energy projects. The current study aims to generate insights into the potential and challenges of integrating Fintech solutions with green financing. This integration is conceptualised in the study as a strategy to facilitate the creation of a more eco-friendly financial environment.